Insights into a Possible Mechanism Underlying the Connection of Carbendazim-Induced Lipid Metabolism Disorder and Gut Microbiota Dysbiosis in Mice. (24th August 2018) - Jin, Cuiyuan; Zeng, Zhaoyang; Wang, Caiyun; Luo, Ting; Wang, Siyu; Zhou, Jicong; Ni, Yingchun; Fu, Zhengwei; Jin, Yuanxiang
Abstract: Carbendazim (CBZ), a systemic, broad-spectrum benzimidazole fungicide, is widely used to control fungal diseases and has been regarded as an endocrine disruptor that causes mammalian toxicity in different target organs. Here, we discovered that chronic administrations of CBZ at 0.2, 1, and 5 mg/kg body weight for 14 weeks not only changed the composition of gut microbiota but also induced significant increases in body, liver, and epididymal fat weight in mice. At the biochemical level, the serum triglyceride (TG) and glucose levels also increased after CBZ exposure. Moreover, the level of serum lipoprotein lipase (LPL), which plays an important role in fatty acid release from TG, was decreased significantly. For gut microbiota, 16S rRNA gene sequencing and real-time qPCR revealed that CBZ exposure significantly perturbed the mice gut microbiome, and gas chromatography found that the production of short-chain fatty acids were altered. Moreover, CBZ exposure increased the absorption of exogenous TG in the mice intestine and inhibited the TG consumption, eventually leading the serum triglyceride to maintain higher levels. The increase of lipid absorption in the intestine direct caused hyperlipidemia and the multi-tissue inflammatory response. In response to the rise of lipid in blood, the body maintains the balance of lipid metabolism in mice by reducing lipid synthesis in the liver and increasing lipid storage in the fat. Chronic CBZ exposure induced the gut microbiota dysbiosis and disturbed lipid metabolism, which promoted the intestinal absorption of excess triglyceride and caused multiple tissue inflammatory responses in mice.